Nonlinear modal interactions in parity-time (PT) symmetric lasers - Ge, Li; El-Ganainy, Ramy (Scientific reports, 2016)
Parity-time symmetric lasers have attracted considerable attention lately due to their promising applications and intriguing properties, such as free spectral range doubling and single-mode lasing. In this work we discuss nonlinear modal interactions in these laser systems under steady state conditions and we demonstrate that several gain clamping scenarios can occur for lasing operation in the -symmetric and -broken phases. In particular, we show that, depending on the system’s design and the external pump profile, its operation in the nonlinear regime falls into two different categories: in one the system is frozen in the phase space as the applied gain increases, while in the other the system is pulled towards its exceptional point. These features are first illustrated by a coupled mode formalism and later verified by employing the Steady-state Ab-initio Laser Theory (SALT). Our findings shine light on the robustness of single-mode operation against saturation nonlinearity in -symmetric lasers.